A new Desmodesmus sp. from the Tibetan Yamdrok Lake. - Jinhu Wang; Qiangying Zhang; Naijiang Chen; Junyu Chen; Jinna Zhou; Jing Li; Yanli Wei; Duo Bu (PLoS ONE, 2022)
Revegetation of exposed sub-soil, while a desirable recovery strategy, often fails due to extreme soil chemical properties, such as low organic matter and pH levels. Microalgae play a key role in maintaining water quality in the lakes and rivers on the Qinghai-Tibet plateau. Plateau microalgae have extensive application prospects in environmental purification, biotechnology, medicine and cosmetics, food industry, and renewable energy. To identify the high biomass of microalgae present in nature, microalgae with the greatest biomass were screened from natural water samples through filtration, pre-culture, and plate scribing separation. Following identification via 18S rRNA sequencing as for the Desmodesmus sp., we constructed a neighbor-joining phylogenetic tree. The novel Desmodesmus sp. from the Tibetan Yamdrok Lake were identified through polyphasic taxonomy. Simultaneously, the sequence of the experimental samples and the target species were shown different following the identification and analysis of SNP and InDel loci. The light-absorbing properties of plateau Desmodesmus sp. have been investigated previously. The characteristic absorption peak of Desmodesmus sp. on the plateau was measured at 689 nm in the visible spectrum using full wavelength scanning with a UV-Vis spectrophotometer. For Desmodesmus sp. which is prone to settling in the process of amplification culture. By monitoring the change trend of total nitrogen, total phosphorus, pH and electrical conductivity in algae solution system, we determined that the logarithmic growth phase and the best transfer window of Desmodesmus sp. were at 15-20 days. This study can provide basic research methods for the study of microalgae in high altitude areas, and lay a foundation for the later study and application of microalgae.